Pediatric Open Globe Injury in Central China - Chen, Hongling; Zhang, Xianliang; Han, Junjun; Jin, Xuemin (Frontiers in Medicine, 2022)
Purpose: To describe the characteristics, managements, and outcomes of pediatric open globe injury (OGI) in central China. Methods: Retrospective chart review of pediatric inpatients diagnosed with OGI between 2017 and 2020 at Henan Eye Hospital. Four hundreds and one eyes of 401 patients younger than 17 years were included in this study. Open globe injury was classified according to the Birmingham Eye Trauma Terminology system (BETT). Age, sex, history, cause, month of trauma, treatment received and outcomes were recorded. Visual acuity was documented according to standard visual acuity chart (decimals). Results: Four hundreds and one eyes of 401 patients were included in the study. The mean age was 6.6±3.4 years with the range from 8 months to 16 years. Open globe injuries (OGIs) occurred most frequently in the 2-8 year age and significant male predominance was noted (70.8%). The incidence of pediatric OGIs was lowest in summer months while it increased in the winter months. The most common type of pediatric OGI was penetration (89.0%). Scissors/knife accounted for 22.0% followed by pen/pencil (15.2%) and wood/bamboo sticks (14.5%) of all the pediatric OGIs. Injuries most frequently involved zone I (76.1%). Initially, 70.8% eyes received primary debridement and wound closure without additional intervention and only one eye with no possibility of anatomical reconstruction received evisceration. After initial management, 198 eyes received subsequent operation, including 44 eyes underwent cataract removal + intraocular lens (IOL) implantation and 24 eyes underwent IOL implantation. Finally, over 6 months of follow-up, 129 eyes (32.2%) got visual acuity (VA) of 0.3-1.5 and 63 eyes (15.7%) got VA of 0.01-0.25 while 11 eyes (2.7%) were eviscerated. Conclusion: This study showed that pediatric OGIs in central china are most seen in 2-8 year age group with significant male predominance. Scissors/knife, pen/pencil and wood/bamboo sticks accounted for over half of all cases. Pediatric OGIs often results in significant vision loss. In some severe cases (2.7%), evisceration was ultimately performed. We should call on the public to pay more attention to their children and build a safer environment for them.